LEARNING MATERIALS IN CHARACTER EDUCATION - Abu Bakar; Anwar Anwar (Jurnal Ilmiah Peuradeun, 2015)
Since in 1976, sociology officially became one of the subjects taught in senior high school programs throughout Indonesia. There are still several major problems in teaching it in particular the lack of locally relevant teaching materials and the lack of teachers with a background in sociology. The aim of this study is to find better ways for the teaching of sociology and for students to learn the principles of sociology and to find the best of teaching materials available for constructing a better paradigm for character education and also to identify the various barriers and difficulties inhibiting the provision of highly successful character education through the study of sociology. Most of the results showed that in teaching sociology in Banda Aceh the implementation of teaching character based on local wisdom has major problems and obstacles. In particular the standardized national education program ending with standardized national final examinations emphasizes rote learning unrelated to the real life of the students. This raises contradictions because the centrally prepared material makes it difficult to introduce local indigenous values, culture and traditions.